2016
DOI: 10.3892/mmr.2016.5884
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol induces cell cycle arrest and apoptosis in human eosinophils from asthmatic individuals

et al.

Abstract: Abstract. Eosinophils exert a number of inflammatory effects through the degranulation and release of intracellular mediators, and are considered to be key effector cells in allergic disorders, including asthma. In order to investigate the regulatory effects of the natural polyphenol, resveratrol, on eosinophils derived from asthmatic individuals, the cell counting Kit-8 assay and flow cytometry analysis were used to determine cell proliferation and cell cycle progression in these cells, respectively. Cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…These data are strengthened by recent evidences demonstrating that eosinophils undergo cell cycle arrest and apoptosis following RSV treatment [ 29 ]. When treated with RSV, eosinophils from asthmatic individuals show an increase in the protein levels of p53 and p21 and, concurrently, reduced protein levels of Cdk2, cyclin A and cyclin E. Apoptosis was induced through the increase in the apoptotic mediators Bim and Bax and the downregulation of Bcl2 [ 29 ].…”
Section: Molecular Targets During Apoptosis Onset In Lymphomassupporting
confidence: 63%
“…These data are strengthened by recent evidences demonstrating that eosinophils undergo cell cycle arrest and apoptosis following RSV treatment [ 29 ]. When treated with RSV, eosinophils from asthmatic individuals show an increase in the protein levels of p53 and p21 and, concurrently, reduced protein levels of Cdk2, cyclin A and cyclin E. Apoptosis was induced through the increase in the apoptotic mediators Bim and Bax and the downregulation of Bcl2 [ 29 ].…”
Section: Molecular Targets During Apoptosis Onset In Lymphomassupporting
confidence: 63%
“…Since long time ago, we have known that dexamethasone induces irreversible G1 arrest and death of a human lymphoid cell line (30). An arrest of cell cycle progression in the G1/S phase also induced apoptosis of human eosinophils from patients with asthma (31). All these together imply a potential role of the G1/S transition in blood cells in response to corticosteroids.…”
Section: Discussionmentioning
confidence: 91%
“…As important processes in the development of allergic diseases, promoting the apoptosis of EOS and reducing the infiltration of EOS into local tissues could potentially relieve local inflammation in allergic diseases (7). IL-3, IL-5 and GM-CSF can promote the survival of EOS (23).…”
Section: Discussionmentioning
confidence: 99%
“…To date there is no cure for AR, therefore, further research is required. Recent studies have demonstrated that eosinophils (EOS) are the primary effector cells in AR, and the localization and activation of a large number of EOS is an important feature of allergic diseases (710). Due to the signaling link between the nasal cavity and bone marrow, a large number of EOS are stimulated by allergens that infiltrate local tissues (11).…”
Section: Introductionmentioning
confidence: 99%